ANALYSIS OF FACTORS INFLUENCING FARMERS’ HOUSEHOLD CONSUMPTION IN MALANG CITY, INDONESIA - S Sugiyanto; Lintar Brillian Pintakami (Agricultural Socio-Economics Journal, 2021)
Food has become a primary human need that must be fulfilled before fulfilling other living needs such as clothing, housing, and education. The present study analyzes food consumption patterns and factors influencing it in the Malang District. The analysis is done by tabulating data and then analyzed using the calculation of energy consumption adequacy based on the DDP reference. To analyze the influencing factors carried out using multiple linear regression analysis. Sampling is done by simple random sampling method as many as 100 housewives. The results indicate that the food consumption patterns of households in the Malang District have not reached ideal numbers. Simultaneously the income variable, the number of family members, the age of the mother, the level of maternal education significantly influence the food consumption patterns of households in Malang District while partially the income and number of families have a significant effect on household food consumption patterns in Malang District City.